The Role of Anatomical Adaptations in Human Bipedalism - Amna Shoaib, Madiha Ali, Fareeha Mushtaq, Muhmmand Saad Abdullah, Ayesha Shahid, Sadia Farooq (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: The human bipedalism is a special type of walking and is characterized by drastic alterations to the organism’s architecture. Understanding these modifications from the vertebral column and pelvis to the lower limbs enable the paleoanthropologists to have a view on how early hominines evolved to anthropology and how the change was required for anthropology to happen and the changes that affected this on human beings.